Acute endophthalmitis and hyphema mimicking pink hypopyon associated with ocular toxocariasis: A case report - Taku Wakabayashi; Rei Kamuro; Noriyasu Hashida; Nobuhiko Shiraki; Hirokazu Sakaguchi; Nobuyuki Ohguro; Kohji Nishida (American Journal of Ophthalmology Case Reports, 2021)
Purpose: To report a case of acute endophthalmitis and hyphema mimicking pink hypopyon associated with ocular toxocariasis. Observations: An immunocompetent 56-year-old woman presented to our hospital with a sudden onset and a three-day history of decreased visual acuity in her left eye. There were no known inciting factors for her symptoms; however, she had a history of eating undercooked beef five days prior. On examination, the best-corrected visual acuity of her left eye was light perception and the intraocular pressure was 24 mmHg. Hyphema mimicking pink hypopyon and vitreous opacity suggestive of acute endophthalmitis were observed in her left eye. The patient underwent an emergency pars plana vitrectomy. The intraoperative findings included iridodialysis, severe vitritis, multiple whitish spots on the retina, white sheathed retinal vessels, and whitish peripheral granuloma. The aqueous humor tap and vitreous tap cultures were negative. Blood tests showed elevated eosinophil and total immunoglobulin (Ig) E levels. Enzyme-linked immunosorbent assay of her intraocular fluid showed positive anti-Toxocara canis IgG reactions; the patient was therefore diagnosed with ocular toxocariasis. Subsequent treatment with oral albendazole and prednisone resulted in significant improvement and recovery of visual acuity to 20/12.5. Conclusions and Importance: Acute endophthalmitis with hyphema mimicking pink hypopyon is a rare clinical presentation of ocular toxocariasis. The findings from this case highlight the importance of suspecting ocular toxocariasis if a patient presents with acute endophthalmitis and hyphema accompanied with peripheral granuloma. Early vitrectomy and subsequent treatment with oral albendazole and prednisone can be effective in visual recovery.